2009
DOI: 10.1007/s00415-009-0149-2
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of vertigo, migraine and vestibular migraine

Abstract: Both migraine and vertigo are common in the general population with lifetime prevalences of about 16% for migraine and 7% for vertigo. Therefore, a concurrence of the two conditions can be expected in about 1.1% percent of the general population by chance alone. However, recent epidemiological evidence suggests that the actual comorbidity is higher, namely 3.2 %. This can be explained by the fact that several dizziness and vertigo syndromes occur more frequently in migraineurs than in controls including benign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
171
0
13

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 245 publications
(203 citation statements)
references
References 56 publications
7
171
0
13
Order By: Relevance
“…Auditory symptoms, including hearing loss, tinnitus, and aural pressure have been reported in up to 38% patients with vestibular migraine. Hearing loss is usually mild and transient, without or with only minor progression in the course of the disease 2,34,35 . Radtke et al reassessed 61 patients with definitive VM according to validated diagnostic criteria after a follow-up time of 9 years and their findings are shown on Table 2 36 .…”
Section: Clinical Presentationmentioning
confidence: 99%
“…Auditory symptoms, including hearing loss, tinnitus, and aural pressure have been reported in up to 38% patients with vestibular migraine. Hearing loss is usually mild and transient, without or with only minor progression in the course of the disease 2,34,35 . Radtke et al reassessed 61 patients with definitive VM according to validated diagnostic criteria after a follow-up time of 9 years and their findings are shown on Table 2 36 .…”
Section: Clinical Presentationmentioning
confidence: 99%
“…The presence of these otoneurologic symptoms indicates activation of vestibular pathways. Dizziness and vertigo often accompany migraine attacks (von Brevern, Zeise, Neuhauser, Clarke and Lempert, 2005;Cutrer and Baloh, 1992;Lance, 2000) and are frequently reported during the headache-free interval (Kuritzy, Ziegler and Hassanein, 1981;Lempert and Neuhauser, 2009;Cha et al, 2009). Indeed, around 25% of migraine sufferers experience episodes of vertigo (Baloh, 1997).…”
Section: Vestibular Instabilitymentioning
confidence: 99%
“…Epidemiological studies suggest that co morbidity of migraine and vertigo is 4.5 % for women and 1.5 % for men [3]. In an analysis of 200 patients from a dizziness clinic, it has been shown that 38 % of patients with dizziness may actually fit into the clinical criteria for migraine [4].…”
Section: Introductionmentioning
confidence: 99%
“…The type of dizziness can be peripheral and central in patients with migraine. Benign paroxysmal positional vertigo (BPPV), Meniere's disease, motion sickness, cerebellar disorders and anxiety syndromes are more frequent in migraineurs than in controls [3].…”
Section: Introductionmentioning
confidence: 99%